U.S. Policy Toward the Israeli-Palestinian Conflict under the Trump Administration: Continuity or Change? - Erdogan, Ayfer; Habash, Lourdes (SETA FOUNDATION, 2020)
The 2017 inauguration of Donald Trump as the US. president opened a new chapter in U.S. policy making toward the Israeli-Palestinian conflict. Several developments that have taken place under the Trump Administration mark a clear rupture from the Oslo Accords in favor of support for Israeli plans to annex a large fraction of the West Bank and design a new settlement of the conflict according to its interests. While the U.S. policy toward the Palestinian issue is not radically different under Trump, he does break from former presidents in that he overtly indicates a sharp pro-Israel tilt and has been more transparent about the U.S. position in the conflict. In light of the developments that have taken place in the last three years, this article aims to investigate the main pillars of the U.S. policy toward the Israeli-Palestinian conflict and to analyze how far the Trump Administration's policies toward the conflict indicate a shift from those of his predecessors. It also offers some insights into the future of the Israeli-Palestinian conflict by providing three prospective scenarios and discussing their repercussions.
Keywords: U.S. Foreign Policy; Israeli-Palestinian Conflict; Trump Administration; Deal of the Century; Government & Law